Bohr Type Inequalities for Functions with a Multiple Zero at the Origin - Ponnusamy, S.; Wirths, K.-J. (Computational methods and function theory, 2020)
Recently, there has been a number of good deal of research on the Bohr’s phenomenon in various settings including a refined formulation of his classical version of the inequality. Among them, in Paulsen et al. (Proc Lond Math Soc 85(2):493–512, 2002) the authors considered cases in which the above functions have a multiple zero at the origin. In this article, we present a refined version of Bohr’s inequality for these cases and give a partial answer to a question from Paulsen et al. (2002) for the revised setting.